If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + 4h = 15h Solving 19 + 4h = 15h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-15h' to each side of the equation. 19 + 4h + -15h = 15h + -15h Combine like terms: 4h + -15h = -11h 19 + -11h = 15h + -15h Combine like terms: 15h + -15h = 0 19 + -11h = 0 Add '-19' to each side of the equation. 19 + -19 + -11h = 0 + -19 Combine like terms: 19 + -19 = 0 0 + -11h = 0 + -19 -11h = 0 + -19 Combine like terms: 0 + -19 = -19 -11h = -19 Divide each side by '-11'. h = 1.727272727 Simplifying h = 1.727272727
| 10x-3=347 | | log(x)=5.4 | | (7x-95)+(3x-38)=45 | | 3x=9x+54 | | -7+6x=-43 | | (15)=-x+7 | | 8x+5=-8(-2x+6)-7 | | X/0.06=300 | | 2.8x+21=2.2x+18 | | (y+12)(2y-9)=0 | | U^2+3U-91=0 | | 4x=-x+35 | | 3w-6+2w=(-2)+w | | 12g+31h=19 | | 48/50=x/10 | | cosx=11/12 | | -27/7=x-3 | | 6c+5=4 | | 600+x(15)=2400 | | x-2.78=4.29 | | 2x+0.5(sin(0.5x))=0 | | 7h+21=6h+18 | | 0.6x+6.6=5.7 | | 2(2x)+2x=90 | | 13x=4(3x-28) | | 45n=82 | | 8d-9-(d+3)= | | 10x-6+10x+4+18y+16y+6=360 | | 40x+15x=673 | | X+3=4w-6 | | 7-c=30 | | 4x-x^2=2 |